2008
DOI: 10.1017/s0033822200033592
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Charcoal Exposed to High and Low Ph: Implications for 14C Sample Preparation and Charcoal Preservation

Abstract: ABSTRACT. Chemical and structural similarities between poorly preserved charcoal and its contaminants, as well as low radiocarbon concentrations in old samples, complicate 14 C age determinations. Here, we characterize 4 fossil charcoal samples from the late Middle Paleolithic and early Upper Paleolithic strata of Kebara Cave, Israel, with respect to the structural and chemical changes that occur when they are subjected to the acid-base-acid (ABA) treatment. Differential thermal analysis and TEM show that acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 28 publications
1
79
0
Order By: Relevance
“…Calcite, however, buffers the ground water to above pH 8, and this is often not conducive to the preservation of charred materials. In fact, the prescreening showed that the charcoal was E 6 2 12 10 T10 T11 21 10 18 5 T12 11 8 8 6 T4 12 3 21 4 T5 12 2 12 6 Totals 64 26 75 33 generally poorly preserved, especially in the eastern part of the cave, which today, at least, is much wetter than the western part (24). We also note that less than half the bones contained acid insoluble collagen.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Calcite, however, buffers the ground water to above pH 8, and this is often not conducive to the preservation of charred materials. In fact, the prescreening showed that the charcoal was E 6 2 12 10 T10 T11 21 10 18 5 T12 11 8 8 6 T4 12 3 21 4 T5 12 2 12 6 Totals 64 26 75 33 generally poorly preserved, especially in the eastern part of the cave, which today, at least, is much wetter than the western part (24). We also note that less than half the bones contained acid insoluble collagen.…”
Section: Discussionmentioning
confidence: 95%
“…The latter proves to be a good indicator of charcoal preservation (24) and in practice determines the yield of clean charcoal and hence whether or not the sample can be dated. Only samples that were well-preserved and free of detectable contaminants were dated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 which a sample will be susceptible to dissolution/oxidation (Bird et al, 2002;Brock and Higham, 2009;Rebollo et al, 2008). In practice this means that some samples rapidly undergo virtually complete dissolution/oxidation, when only a small proportion of the material that is lost in pre-treatment is likely to be an exogenous contaminant.…”
Section: MI Bird Et Al -Plasma Ashing Pre-treatment For Radiocarbomentioning
confidence: 99%
“…It has been reported that the characteristics of a very old wood charcoal sample are different from those of modern wood charcoal according to its state of preservation (Cohen-Ofri et al 2006;Rebollo et al 2008). It can be assumed that these differences may lead to some difficulties when radiocarbon dating very old wood charcoal samples.…”
mentioning
confidence: 99%